The impact of climate and land use changes on nitrogen and phosphorus pollution in the Luhun Lake Basin, China - Yang, Xu; Qiu, Shike; Wang, Chao; Hao, Limin (Frontiers in Earth Science, 2024)
Water is an important ecological factor, and non-point source pollution (NPSP) seriously affects water security. In recent years, NPSP has affected water security and human survival in China. The Luhun Lake Basin has been selected as an example region of Yellow River Basin (YRB) in China, and the trends and impacts of nitrogen (N) and phosphorus (P) has been quantitatively evaluated. The results show that (1) the arable land and water bodies decreased, while forest land, grass land, construction land and unutilized land increased in the 20 years. The average annual precipitation increased from the northeast to the southwest in the 20 years; (2) the N and